VALIDITAS MODEL PEMBELAJARAN GROUP SCIENCE LEARNING; PEMBELAJARAN INOVATIF DI INDONESIA - Prahani, Binar Kurnia; Nur, Mohammad; Yuanita, Leny; Limatahu, Iqbal (Vidya Karya, 2016)
Abstract: Result of a preliminary study showed that in general the collaborative problem solving skills, science process skills, and confidence of students of SMA Negeri 19 Surabaya, SMAN 1 Tegaldlimo, MA Roudlotun Nasyin Mojokerto are still low. Therefore, researchers developed a model instructional group science learning to enhance collaborative problem solving skills, science process skills, and confidence. The purpose of this research is to get validity of Group Science Learning (GSL) developed to improve collaborative problem solving skills, science process skills, and confidence. Methods of data collection validation using Focus Group Discussion (FGD). Group science learning model developed needs to be validated by experts through Focus Group Discussion (FGD). Group science learning model assessed the validity of the learning model based on content validity and construct validity. Results of the validation by experts through focus group discussions indicate that group science learning model to improve the collaborative problem solving skills, science process skills, and confidence in this study are included in the category of very valid. This group science learning model can be implemented in learning to improve the collaborative problem solving skills, science process skills, and confidence. Keywords: content validity, construct validity, and group science learning model Abstrak: Hasil studi awal menunjukkan bahwa secara umum keterampilan pemecahan masalah kolaboratif, keterampilan proses sains, dan kepercayaan diri siswa SMA Negeri 19 Surabaya, SMA Negeri 1 Tegaldlimo, MA Roudlotun Nasyin Mojokerto masih rendah. Oleh karena itu peneliti bermaksud mengembangkan model group science learning. Tujuan penelitian ini adalah untuk mendapatkan validitas model Group Science Learning yang dikembangkan untuk meningkatkan keterampilan pemecahan masalah kolaboratif, keterampilan proses sains, dan kepercayaan diri. Metode pengumpulan data validasi menggunakan Focus Group Discussion (FGD). Validitas model pembelajaran Group Science Learning dinilai berdasarkan validitas isi dan validitas konstruk. Hasil validasi oleh pakar melalui FGD menunjukkan bahwa model Group Science Learning untuk meningkatkan keterampilan pemecahan masalah kolaboratif, keterampilan proses sains, dan kepercayaan diri dalam penelitian ini termasuk dalam kategori sangat valid. Model Group Science Learning dapat diimplementasikan dalam pembelajaran untuk meningkatkan keterampilan pemecahan masalah kolaboratif, keterampilan proses sains, dan kepercayaan diri.Kata Kunci: Validitas isi, validitas konstruk, dan group science learning model